(3egL GdOYhGJ hefgL GdYfGjGJs - (3GdWGhSj, GdMSfj, CHh GdbGSe, QVi GdnqOjf, Ydj Hf ehSi Hf LYaQ Hf WGhhS, J (B664 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3PcQ eG GNJQfGg ef GMQGR GdfHj hGdCFeI UdhGJ GddY Ydjg hYdjge GLejYf , MQR GdfHj Udi Gddg Ydjg hSde QhGg CHh GdMSf Ydj Hf eMeO Hf Ydj Hf YHO GdUeO (B...s
(3BNQgG (B:s
... (3hJQOjge aj eghi MajQge hGQege HMLQge hRcge HeTGbUge hGcHge Ydi efGNQge hGNfbge HhJQge hGQOO cjOge aj fMhQge (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\26s
(3cTa GdXfhf (B2\1911s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs